Effects of epidermal growth factor on the proliferation and cell cycle regulation of cultured human amnion epithelial cells - Fatimah S.S.; Tan G.C.; Chua K.H.; Tan A.E.; Hayati A.R. (2024)
Indexed by SCOPUS/WOS